Perbedaan Kadar Air Pada Ikan Kembung (Rastrelliger brachysoma) Asap Berdasarkan Ukuran Ikan Yang Berbeda - Bahrudin, Mohammad; Sholiha, Illiyatus (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2022)
Fish is a source of high protein and is a commodity that is prone to spoilage. One method to inhibit the decay process is by smoking. Smoking aims to reduce the water content of smoked fish so that the smoked fish can have a longer shelf life. One of the commonly smoked fish is mackerel (Rastrelliger brachysoma). This method of smoking mackerel in this study is using traditional smoking method with coconut shells as fuel. The purpose of this study was to determine the difference in water content in smoked mackerel based on different fish size according to SNI 2725:2013 regarding smoked fish. This type of research is quantitative experimental with the independent variable being the size of mackerel (A = size of mackerel 10 cm – 12 cm and B = size of mackerel 16 cm – 18 cm), the independent variable is water content, while the controlled variable is the type of fish and length of smoking time. Each treatment was repeated 5 times. The result of this study is that there are differences in water content of smoked mackerel based on different fish sizes, where Fcalculated (82,73) > from Ftable 5% (5,31) and small (A = size of mackerel 10 cm – 12 cm) and medium size (B = size of mackerel 16 cm – 18 cm) smoked mackerel meet the SNI 2725:2013 quality standard on smoked fish for the water content parameter, which is below the maximum value of 60% water content.